New Results and Advances in PGE Mineralogy in Ni-Cu-Cr-PGE Ore Systems - Barkov, Andrei Y. (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The book (Special Issue) presents impressive new results related to a wide spectrum of occurrences of platinum-group minerals (PGM) and natural compounds enriched in platinum-group elements (PGE), which are associated with various complexes and deposits, such as Uralian-Alaskan-type complexes, layered intrusions and placers. The geographical locations of the involved deposits and complexes include, on a truly international scale, different areas of the Urals, Western and Eastern Sayans and Gornaya Shoria in Siberia, Southern Central Asian Orogenic Belt in China, Northern Michigan, USA, South Africa and Zimbabwe, etc. Of particular interest is the first description of a new species of PGM, thalhammerite (approved by the Commission on New Minerals, Nomenclature and Classification of the International Mineralogical Association), which is a new species of palladium-silver sulfobismuthide discovered in the Noril'sk region of Russia. Additionally, comprehensive reviews, on compositional variations in Pt-Fe alloy minerals and processes of transformations of PGM in exogenic environments, are presented which will also attract attention from international readers.